he association of total and abdominal obesity with Health-Related Quality of Life in a sample of Greek healthy adults (Epidemiology, Biostatistics, and Public Health, 2022)
Background: in the Greek population, the association between obesity and Health-Related Quality of Life (HRQoL) has not been examined so far. Thus, the purpose of the present study is to explore obesity-related predictors of HRQoL in a sample of Greek healthy adults.Methods: a cross-sectional design was used. The sample consisted of three hundred twenty seven healthy men (N=105) and women (N=222), between the ages of 30 and 50 years (mean age=39.57 ± 6.68) who lived in Athens. Body mass index (BMI), waist to hip ratio (WHR), and body fat (BF) were assessed. HRQoL was evaluated using the short-form 36 (SF-36) health survey, which consists of eight subscales and two health factors (physical and psychological health). Socio-demographic variables and health-related behaviours were assessed by questionnaires. Separate hierarchical regression analyses were conducted to examine the associations between BMI, WHR, BF and SF-36 health survey subscales and factors.Results: socio-demographic and health-related variables were moderately associated with the HRQoL subscales and factors. Furthermore, after controlling the socio-demographic variables and health-related behaviours, (a) BMI negatively predicted the physical functioning, physical role, bodily pain, and social functioning subscales, as well as the physical health factor and (b) WHR and BF negatively predicted the physical functioning subscale. However, the obesity indexes did not predict other psychological health subscales.Conclusions: the results indicated negative associations of BMI, WHR, BF with physical functioning and health in a sample of Greek healthy adults. Such data relating total and abdominal obesity to HRQoL, as assessed by BMI, WHR, and BF, have not been reported until now in the literature. One limitation of this study was that the sample size was relatively small and the results could not be generalized to the entire Greek population.